Challenging ’Derivative’ Explanations of Scientific Racism: The Case of Dr. J.C. de Man (1818-1909) - Schipper, Douwe (Studium, 2017)
This article evaluates the historiography of late nineteenth-century sciences of race. A key aspect of this historiography is the idea that sciences of race were designed specifically to justify preexisting ideas about race. This aspect is defined as the ‘derivative explanation of scientific racism’. I critique this explanation by focusing on one specific science of race, craniometry, and using one particular craniometrist, Dr. J.C. de Man (1818–1909), as a case study. I argue, first, that historians of the derivative explanation cause confusion because they apply current racial language in their characterization of craniometry of the past; second, that they overlook the emerging ideal of objectivity in science; third, that they tend to reduce social motivations for practicing science to being racial by definition.